Tumpeng Sewu: Osing tradition as cultural material in social studies learning - Dwijayanti, Kartika; Khirani, Nailyviatul Mazdha; Wijayanti, Noveka Suti; Ependi, Ra’i Anisa Samia Wahyi Putri (Jurnal Teori dan Praksis Pembelajaran IPS, 2023)
This study aims to explore social studies teaching materials based on the Tumpeng Sewu tradition of the Osing tribe. A qualitative approach was used by conducting interviews with informants and strengthen by relevant previous research. The results showed that the culture of Tumpeng Sewu became one of the hereditary cultures of the Banyuwangi people, especially the people in Kemiren Village. This culture is a culinary festival of Tumpeng Sewu in a traditional clean village ritual in Kemiren Village, Banyuwangi. This traditional ritual is carried out by the Osing ethnic group and is held every year by serving food dishes as a form of their traditional tradition. This custom may be great in attracting tourists and improving the economic aspects of the community. The culinary festival is an annual program of the Banyuwangi government which has been held from 2015 to 2019, even though it is hindered by a pandemic, this ritual continues even though the procession is slightly different. The contribution of this research is used as cultural material in social studies learning which refers to literacy studies and interviews with resource persons.